POLICY EVALUATION OF PURCHASING ELECTRICITY FROM ROOFTOP PV BY PT PLN (PERSERO) AND ITS EFFECTIVENESS IN INCREASING THE RENEWABLE ENERGY PORTION ON THE ENERGY MIX - Andika Bayu Kurniawan, R
Solar Photovoltaic (PV) technology, which converts sunlight into electricity is a rapidly growing renewable energy resource, and assumedly will be a major role in global energy production. Solar energy is abundant and therefore Solar PV is one of the most promising renewable energy resources. In 2017, cumulative solar PV capacity reached almost 398 GW and generated over 460 TWh, representing around 2% of global power output. Utility-scale projects account for just over 60% of total PV installed capacity, with the rest in distributed applications (residential, commercial and off-grid). Over the next five years, solar PV is expected to lead renewable electricity capacity growth, expanding by almost 580 GW. However, the growth in Indonesia is not as enthusiastic as what its peers does. In 2017, total installed solar power plant in Indonesia is merely just 0.017 GWp from potential capacity of 207,9 GWp (RUEN), while an overall primary energy mix of renewable energy is 7.3%. Compared to 23% target of primary energy mix in 2025, there is so much thing government must do. Hence one of the efforts to push the development of solar PV capacity, government stipulated Minister of Energy and Mineral Resources Regulation Number 49 of 2018 on Solar Photovoltaic System Utilization by customers of PT PLN. The calculation of the export-import value of energy as per Minister of Energy and Mineral Resources Regulation Number 49 of 2018 is determined that the maximum capacity of Rooftop PV that can be installed is 100% of the power connected to the National Electric Company PLN. From this capacity, the energy exported to the grid is valued at 65% of the actual export. This provision applies to non-industry customers, while for industrial customers, it is subject to capacity charge and emergency energy charge costs following the provisions of the Minister of Energy and Mineral Resources Regulation Number 01 of 2017 on Parallel Operation of Power Plants with the PT PLN (Persero) Electric Power Network. The objectives of this research are to evaluate the implementation of the rooftop PV policy and observe the its attractiveness, where with the value of the conversion factor applied, is it optimal enough. Then to assess some sensitivity to potential energy savings from the customer side and from the utility side. Next is to be able to provide recommendations that can be optimized in an effort to overcome the existing problems, including conducting a review of similar schemes that are practiced in other countries. The basis of this research exploration is an evaluation or review of public policies that have been implemented, so the program evaluation method is used. Evaluation is carried out in a number of steps, namely defining stakeholders, describing policies, compiling the evaluation focus, collecting credible data, conducting analysis, and drawing conclusions and alternative solutions. Data obtained through interviews, focus group discussions, as well as literature reviews from books, journals, publications, and other reliable sources. The analysis is done qualitatively and also simulates various sensitivity scenarios to calculate the potential savings that might be obtained by the customer. From the analysis, several recommendations are obtained, namely the application of a 1:1 conversion factor to attract more household consumers, that are surely less commercial, eliminate capacity costs and emergency energy costs for industrial consumers but still implementing 1:0.65 conversion factor, apply the installed capacity quota by taking into account the strength of the network, and immediately making a distribution grid code as a basis for reviewing technical studies of applications for PV rooftop installation. In addition, it is necessary to introduce technology which can support network quality infrastructure in facing intermittent disruption from renewable energy generators in general, and from rooftop PV in particular. Another thing that needs to be explored is the peer-to-peer energy trade between consumers and consumers who installed rooftop PV (prosumers), where this is possible using blockchain technology. Several alternative solutions that exist in this study are expected could be reviewed by respective agency and stakeholders. In the bigger picture, the recommendations are also expected could help us reaching the target of 23% Renewable Energy in 2025 as mandated in RUEN, through better policy on utilizing rooftop PV technology that benefitted not only the consumers, but also utilities and people of Indonesia.